(untitled) (Bangladesh Journal of Physics, 2024)
From its commissioning, it was required to ensure the nuclear or radiological safety of the BAEC TRIGA Mark-II Research Reactor according to the country-specific regulatory guidance (BAERA) or followed by any international guidance (US NRC or IAEA). It is always important to take protective actions not to commit enough radiological doses. Therefore, the present work focused on the core inventory and radiological dose assessment due to a hypothesized research reactor accident of TRIGA Mark-II at Savar, Dhaka, Bangladesh. The core inventory and source term of five radionuclides (137Cs, 131I, 133Xe, 85mKr, and 90Sr) were studied using the ORIGEN 2.1 code until December 2021. These radionuclides were chosen due to their high emission characteristics from a nuclear accident. The dose values of TED, ground deposition, and organs were calculated for an 80 km radius from the reactor site using the HotSpot 3.1.2 code and meteorological data of six seasons of Bangladesh. The assessed dose values are compared and it is shown that dose values in the rainy season are highest due to the rainout coefficient. The other five seasonal TEDE data show similar dose patterns and are also high enough to the permissible limit of dose values. So, regardless of the time of year, if an accident occurs, it is necessary to immediately take preventive radiological measures based on the local authority emergency response plan. Bangladesh Journal of Physics, Vol. 31, Issue 2, pp. 65 – 74, December 2024